2017
DOI: 10.1016/j.eurpsy.2017.02.099
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cerebral Blood Flow Measured with SPECT in Patients with First Episode Psychosis

Abstract: IntroductionSingle-photon emission computed tomography (SPECT) is a valid method for measuring regional cerebral blood flow (rCBF). Recent studies regarding rCBF in patients with first episode psychosis (FEP) reported heterogeneous results, but were limited with small sample size. Neuroimaging can help us in setting the diagnosis of illness, as well as in following the progress and finding more effective treatment for psychotic disorders.ObjectivesTo compare, baseline alterations of the rCBF using SPECT with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…functional magnetic resonance imaging (fMRI)] and recently with ASL (Hill et al, 2004 ; Kindler et al, 2015 ). Interestingly previous studies using PET and SPECT in unmedicated FEP revealed reduced cortical perfusion and metabolism (Brewer et al, 2007 ; Makarić et al, 2017 ; Molina et al, 2005 ). Our results corroborate and extend this evidence by showing the existence of lower frontal cortical absolute perfusion in FEP without the potential confound of antipsychotic treatment using MRI.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…functional magnetic resonance imaging (fMRI)] and recently with ASL (Hill et al, 2004 ; Kindler et al, 2015 ). Interestingly previous studies using PET and SPECT in unmedicated FEP revealed reduced cortical perfusion and metabolism (Brewer et al, 2007 ; Makarić et al, 2017 ; Molina et al, 2005 ). Our results corroborate and extend this evidence by showing the existence of lower frontal cortical absolute perfusion in FEP without the potential confound of antipsychotic treatment using MRI.…”
Section: Discussionmentioning
confidence: 91%
“…The effect of antipsychotics on cortical perfusion is even less understood. Studies using PET and single photon emission computed tomography (SPECT) found consistently reduced perfusion and metabolism in the frontal cortex in both medicated and unmedicated patients with SCZ (Makarić et al, 2017 ; Molina et al, 2005 ). Viviani et al ( 2013 ) found decreased cortical perfusion after amisulpride administration in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%